SETTING OF PLANTATION LAND AREA LIMITATION BASED ON SOCIAL FUNCTION PRINCIPLES OF LAND CULTIVATION RIGHTS TO REALIZE SOCIAL WELFARE-PROMOTING PLANTATION - Lego Karjoko (Faculty of Law, Universitas Jenderal Soedirman, 2017)
The existence of large plantations in Indonesia has proven the failure of individualism value to uphold agrarian justice. This study aims to examine regulations regarding to the land ownership which contradicts with social function principles of Land Cultivation Rights (LCR) and provide recommendation for setting the land ownership which can realize land utilization for plantation ideally. This study employs normative legal research method by statute and conceptual approach. The legal materials were analyzed by inductive, deductive and interpretative syllogism. The results of this research are as follows. First, regulations on Site Permit, Plantation Operation Permit and Release of Forest Area for Plantation based on utilitarian justice and concentrative land ownership are not in accordance with social function principles of Land Cultivation Rights (LCR). Second, the setting of maximum ownership for plantation companies should be based on their type of plants and given fully assets that enable the plantation companies to use the land optimally.Keywords: Land Cultivation Rights, cultivation land area, people’s welfare